Pengaruh Leverage sebagai Pemoderasi Hubungan GCG, CSR dan Agresivitas Pajak terhadap Financial Disstress pada Perusahaan Perbankan Syariah di Indonesia - Kusumaningdiah Retno Setiorini; Fitri Fidayanti; Nawang Kalbuana; Pandu Adi Cakranegara (Forum Kerjasama Pendidikan Tinggi, 2022)
This study aims to see the effect of GCG, CSR and Tax Aggressiveness on Financial Distress with Leverage as Moderation in Islamic Banking Companies in Indonesia listed on the IDX from 2015-2019. The sampling technique used in this research is purposive sampling technique and for data analysis using multiple linear analysis techniques. This study reveals that GCG has no significant effect on Financial Distress, CSR has a positive and significant effect on Financial Distress, Tax Aggressiveness has no significant effect on Financial Distress, Leverage has no significant effect on the effect of GCG on Financial Distress, Leverage has a positive effect on the effect of CSR on Financial Distress, Leverage has no effect on the effect of tax aggressiveness on financial distress